Reviewing the Foreign Policy of the Republic of Indonesia Through President Jokowi's Visit to South Africa in 2023 - Indrayana, Rivaldi Zakie (Parahyangan Center for International Studies, 2024)
In August 2023, President Joko Widodo visited several African countries i.e. The Republic of Kenya, United Republic of Tanzania, The Republic of Mozambique and The Republic of South Africa. It was his first visit to Africa during his term since 2014. While the visit covered four African countries, this article discusses only his visit to South Africa where he attended the BRICS forum. In particular this article focuses on Indonesia’s multilateral diplomacy in the BRICS’ forum, the position of Indonesia in the global political stage and its role both at the global and regional levels. Despite Indonesia not yet becoming a member of BRICS, its presence in the BRICS forum in South Africa in 2023 shows that Indonesia’s position in the global political stage has been increasing. Moreover, the presence also opened an opportunity for Indonesia to establish the new direction of its foreign policy and diplomacy not only among BRICS member states but also with South Africa and other African countries for achieving the objective and interest of global in the future was very dynamic in everytime. Keywords: President Joko Widodo; Indonesia; South Africa; Africa; BRICS